2021
DOI: 10.7759/cureus.17164
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of the Neutrophil-Lymphocyte Ratio and the Platelet-Lymphocyte Ratio With Pathological Findings in Neuroendocrine Tumors

Abstract: Introduction The relationship between clinical prognostic factors and blood neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) in some tumors has been investigated. In this study, we examined whether there is a relationship between pathological prognostic factors and NLR as well as PLR only in neuroendocrine tumors (NETs). Methods A total of 115 patients with a NET diagnosis between 2014-2020 were included in the study. The efficiency of NLR and PLR in predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In recent years, indicators, such as neutrophil–lymphocyte ratio (NLR) and platelet–lymphocyte ratio (PLR), calculated on the basis of inflammatory markers circulating in the blood, have aroused interest [ 134 ]. An association between high NLR and tumor size, stage, high grade, shorter survival in NEN patients has been observed.…”
Section: Inflammatory Factors In Gep-netmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, indicators, such as neutrophil–lymphocyte ratio (NLR) and platelet–lymphocyte ratio (PLR), calculated on the basis of inflammatory markers circulating in the blood, have aroused interest [ 134 ]. An association between high NLR and tumor size, stage, high grade, shorter survival in NEN patients has been observed.…”
Section: Inflammatory Factors In Gep-netmentioning
confidence: 99%
“…However, some studies do not support the importance of PLR as a predictor of the presence of metastases or multifocal disease [ 137 ]. Kulahci et al [ 134 ], based on retrospective studies performed in 2014–2020 on patients with NETs, found a correlation between a higher NLR value (cut-off value above 3.01) and tumor location, higher histological grade, increased mitosis, higher Ki-67 proliferation index, metastases, and lymphatic involvement. In the case of PLR, no such correlations have been observed.…”
Section: Inflammatory Factors In Gep-netmentioning
confidence: 99%
“…These factors are very costly to be used as a screening tool. Thus, there is a need to find a reliable marker for the early detection of diabetic complications [3].…”
Section: Introductionmentioning
confidence: 99%